Advances on Innate Immune Evasion by Avian Immunosuppressive Viruses - Wang, Hongnuan; Li, Wei; Zheng, Shijun J. (Frontiers in Immunology, 2022)
Innate immunity is not only the first line of host defense against pathogenic infection, but also the cornerstone of adaptive immune response. Upon pathogenic infection, pattern recognition receptors (PRRs) of host engage pathogen-associated molecular patterns (PAMPs) of pathogens, which initiates IFN production by activating interferon regulatory transcription factors (IRFs), nuclear factor-kappa B (NF-κB), and/or activating protein-1 (AP-1) signal transduction pathways in host cells. In order to replicate and survive, pathogens have evolved multiple strategies to evade host innate immune responses, including IFN-I signal transduction, autophagy, apoptosis, necrosis, inflammasome and/or metabolic pathways. Some avian viruses may not be highly pathogenic but they have evolved varied strategies to evade or suppress host immune response for survival, causing huge impacts on the poultry industry worldwide. In this review, we focus on the advances on innate immune evasion by several important avian immunosuppressive viruses (infectious bursal disease virus (IBDV), Marek's disease virus (MDV), avian leukosis virus (ALV), etc.), especially their evasion of PRRs-mediated signal transduction pathways (IFN-I signal transduction pathway) and IFNAR-JAK-STAT signal pathways. A comprehensive understanding of the mechanism by which avian viruses evade or suppress host immune responses will be of help to the development of novel vaccines and therapeutic reagents for the prevention and control of infectious diseases in chickens.